Kinesiophobia in patients with coronary heart disease: a Rodgers’ evolutionary concept analysis - Zhang, Mei-Jun; Liu, Si; Xiong, Xiao-Yun; Liu, Meng-Die; Xiang, Qin (Frontiers in Psychology, 2025)
IntroductionResearch on kinesiophobia in coronary heart disease is increasing, but existing studies primarily adopt concepts from the chronic pain domain, neglecting the specific characteristics of coronary heart disease patients. This gap limits effective identification and management.ObjectiveThis study aims to clarify the concept of kinesiophobia in coronary heart disease using Rodgers’ evolutionary concept analysis.MethodologyRodgers’ evolutionary concept analysis method was applied to review the literature. A comprehensive search was conducted in PubMed, Web of Science, PsycINFO, CINAHL, Cochrane Library, Embase, Scopus, ProQuest, OVID, CNKI, Wanfang Data, CBM, and VIP Database (up to June 30, 2024). Inclusion criteria: Studies on coronary heart disease patients, addressing the concept’s attributes, antecedents, and consequences, published in English or Chinese. Exclusion criteria: Unavailable full text, gray literature, non-peer-reviewed texts, and study protocols.ResultsA total of 31 articles were included. The attributes of kinesiophobia in coronary heart disease patients were identified as self-symptomatic distress, complex emotional responses, subjective avoidance behavior with personality tendencies, and misperceptions with negative reactions. Antecedents included sociodemographic, disease-related, and psychological factors. Consequences encompassed reduced participation in cardiac rehabilitation, decreased functional capacity, increased major adverse cardiac events, and lower quality of life.ConclusionIn this study, we found that kinesiophobia in patients with coronary heart disease is a subjective avoidance behavior that includes both “fear of pain or weakness” and “fear of cardiac events” based on personality tendencies, driven by complex emotional responses and misperceptions based on their own symptomatic disturbances, and presents an excessive and irrational fear of movement. This analysis highlights the need for early identification and multidisciplinary interventions tailored to this population. It also provides a foundation for developing more specific and objective assessment tools.